A Statistical Study of Verifiable Ideal Standard Based on the Expected Number of Exceedances in Dehradun - Bhatt, Praveen Kumar; Kumar, Sudesh; Nehra, Ankur (International Journal of Computer Sciences and Engineering, 2024)
The development of a Statistically Verifiable Ideal Standard (SVIS) is achieved with the assistance of the Neyman Pearson speculation testing outline function, where we have built SVIS for different toxins given P(X) (or quantile of request ) where X is the convergence of specific contamination. By an exceedance, we imply that the level of a toxin is more prominent than a given edge esteem put somewhere near the controller. As such, if irregular variable T is the contamination level and U is the given edge esteem then the occasion (T > U) is called an exceedance. With the assistance of this SVIS rule, we will check the consistency status of different observing locales in Dehradun city for which information is gathered by the Uttarakhand Pollution Control Board (UPCB). Locales are Ghanta Ghar, Ballupur Flyover, Prem Nagar Chowk, Raipur Road, Mussoorie Road, Dharampur Haridwar Road